Electrically Reliable Perovskite Photovoltaic Cells Against Instantaneous Kilovolt Stress. Issue 3 (5th December 2022) - Park, Junhyoung; Byeon, Junseop; Jang, Jihun; Ko, MyeongGeun; Ahn, Namyoung; Choi, Mansoo; Song, Hyung‐Jun
Abstract: The electrical stability of perovskite solar cells (PSCs) will play an essential role in their commercialization because field‐installed PSCs frequently operate under non‐ideal voltages. Particularly, an instantaneous extremely high voltage (IEHVs) from electro‐static discharge will be applied to PSCs due to friction in roll‐to‐roll processes. In addition, lightning strikes and surges from grids are plausible sources of IEHVs to field‐installed PSCs. Hence, the effect of IEHVs on PSCs is systematically investigated and a robust device structure is suggested. An IEHV severely deteriorates PSCs by destroying their diode characteristics. Physical and chemical damage from IEHVs to the interface between the perovskite film and buffer layers causes increased recombination losses and series resistance. To reinforce the heterointerface, a well‐known surface defect passivation method is adopted, adding excessive PbI2 to perovskite films. The excessive PbI2, mainly located at the interface, successfully protects PSCs from IEHV. Moreover, inserting well‐established defect passivation layers, C60, and phenethylammonium iodide into the interface of a perovskite film improves the device's stability against IEHV. Therefore, interface defect passivation is viable for stable PSCs against abnormal electrical stress. It is believed that this study will provide fundamental insights for designing electrically reliable PSCs, which is crucial for grid‐connected, field‐installed energy generation sources. Abstract : Grid‐connected perovskite solar cells (PSCs) must frequently work under non‐ideal voltages. During surges or lightning strikes, they may also experience instantaneous extremely high voltages (IEHVs). IEHVs physically and chemically deteriorate the surface of perovskite films, resulting in increased recombination loss in the PSCs. Surface passivation can make PSCs durable to IEHV and keeps their efficiency after IEHV stress.